PENGARUH MODEL SAVI TERHADAP KEMAMPUAN KOMUNIKASI MATEMATISPESERTA DIDIKSMA - Suci Windri Handriani (Departemen Matematika, 2018)
Ability of matematical comunication is one of cognitif ability which expected to be owned by the learners in learning mathematic. In fact, the ability of matematical comnunication of learners andlearning activities of students of grade XI MIA SMA Negeri 4 Padang still low, it need to be improve. One of the way to improve the mathematicall communication ability and the learning activities of students is by applaying the SAVI (Somatic, Auditory, Visual, and Intellectual) learning mode. The aim of this study is to describe students mathematical comunication ability by applying SAVI learning mode and student’s mathematical comunication ability by using konvensional learning mode also, and learning activities of studens XI MIA SMA Negeri 4 Padang. We can pull of the conclusion base on the analysis of test, in can be conlude that, the ability of the mathematical comunication of students which use the SAVI learning mode is better compare to the students’ mathematical comunication ability by applaying the convensional learning mode.Keywords –Mathematical comunication ability, Learning activities of students,SAVIlearning mode,Conventional Learning